Conformational Transitions of Subunit ɛ in ATP Synthase from Thermophilic Bacillus PS3 - Feniouk, Boris A. (The Biophysical Society, 2010)
Subunit ɛ of bacterial and chloroplast F(O)F(1)-ATP synthase is responsible for inhibition of ATPase activity. In Bacillus PS3 enzyme, subunit ɛ can adopt two conformations. In the “extended”, inhibitory conformation, its two C-terminal α-helices are stretched along subunit γ. In the “contracted”, noninhibitory conformation, these helices form a hairpin. The transition of subunit ɛ from an extended to a contracted state was studied in ATP synthase incorporated in Bacillus PS3 membranes at 59°C. Fluorescence energy resonance transfer between fluorophores introduced in the C-terminus of subunit ɛ and in the N-terminus of subunit γ was used to follow the conformational transition in real time. It was found that ATP induced the conformational transition from the extended to the contracted state (half-maximum transition extent at 140 μM ATP). ADP could neither prevent nor reverse the ATP-induced conformational change, but it did slow it down. Acid residues in the DELSEED region of subunit β were found to stabilize the extended conformation of ɛ. Binding of ATP directly to ɛ was not essential for the ATP-induced conformational change. The ATP concentration necessary for the half-maximal transition (140 μM) suggests that subunit ɛ probably adopts the extended state and strongly inhibits ATP hydrolysis only when the intracellular ATP level drops significantly below the normal value.